Determination of the strength parameters of pinewood based on the non-destructive sclerometric test with a wood hammer - Szostak, Bartosz; Trochonowicz, Maciej; Kowalczyk, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To assess the technical condition of a structure and design it using existing elements, it is necessary to know its parameters. For existing facilities, it is often not possible to get a sample of material and examine it directly in the laboratory. For this reason, in situ nondestructive testing is very important. The main goal of the paper is to present the issues related to determining the strength parameters of a particular wood based on the non-destructive sclerometric test performed with a wood sclerometric hammer. The study also presents the results of the impact of pinewood density on its compressive strength.
Keywords: pinewood; non-destructive tests; sclerometric test; compressive strength; drewno sosnowe; testy nieniszczące; testy sklerometryczne; wytrzymałość na ściskanie